Performance of a targeted cell‐free DNA prenatal test for 22q11.2 deletion in a large clinical cohort. (1st October 2021) - Bevilacqua, E.; Jani, J. C.; Chaoui, R.; Suk, E.‐K. A.; Palma‐Dias, R.; Ko, T.‐M.; Warsof, S.; Stokowski, R.; Jones, K. J.; Grati, F. R.; Schmid, M.
ABSTRACT: Objective: 22q11.2 deletion is more common than trisomies 18 and 13 combined, yet no routine approach to prenatal screening for this microdeletion has been established. This study evaluated the clinical sensitivity and specificity of a targeted cell‐free DNA (cfDNA) test to screen for fetal 22q11.2 deletion in a large cohort, using blinded analysis of prospectively enrolled pregnancies and stored clinical samples. Methods: In order to ensure that the analysis included a meaningful number of cases with fetal 22q11.2 deletion, maternal plasma samples were obtained by prospective, multicenter enrolment of pregnancies with a fetal cardiac abnormality and from stored clinical samples from a research sample bank. Fetal genetic status, as evaluated by microarray analysis, karyotyping with fluorescence in‐situ hybridization or a comparable test, was available for all cases. Samples were processed as described previously for the Harmony prenatal test, with the addition of DANSR (Digital Analysis of Selected Regions) assays targeting the 3.0‐Mb region of 22q11.2 associated with 22q11.2 deletion syndrome. Operators were blinded to fetal genetic status. Sensitivity and specificity of the cfDNA test for 22q11.2 deletion were calculated based on concordance between the cfDNA result and fetal genotype. Results: The final study group consisted of 735 clinical samples, including 358 from prospectively enrolled pregnancies and 377 stored clinical samples. Of 46 maternal plasma samples from pregnancies with a 22q11.2 deletion, ranging in size from 1.25 to 3.25 Mb, 32 had a cfDNA result indicating a high probability of 22q11.2 deletion (sensitivity, 69.6% (95% CI, 55.2–80.9%)). All 689 maternal plasma samples without a 22q11.2 deletion were classified correctly by the cfDNA test as having no evidence of a 22q11.2 deletion (specificity, 100% (95% CI, 99.5–100%)). Conclusions: The results of this large‐scale prospective clinical evaluation of the sensitivity and specificity of a targeted cfDNA test for fetal 22q11.2 deletion demonstrate that this test can detect the common and smaller, nested 22q11.2 deletions with a low (0–0.5%) false‐positive rate. Although the positive predictive value (PPV) observed in this study population was 100%, the expected PPV in the general pregnant population is estimated to be 12.2% at 99.5% specificity and 41.1% at 99.9% specificity. The use of this cfDNA test to screen for 22q11.2 deletion could enhance identification of pregnancies at risk for 22q11.2 deletion syndrome without significantly increasing the likelihood of maternal anxiety and unnecessary invasive procedures related to a false‐positive result. © 2021 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Jing and Li. Click here to view the Correspondence.